Film for metal lamination molding

By using an extremely thin polyethylene naphthalate (PEN) film to control its thickness and heat shrinkage, the deficiencies in corrosion resistance and adhesion of the thermoplastic resin film for metal tanks are solved, and high corrosion resistance and low cost effects are achieved in acidic environments.

JP7627997B2Active Publication Date: 2025-02-07TOYOBO CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2018103299
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-05-30
Publication Date
2025-02-07
Estimated Expiration
2038-05-30

AI Technical Summary

Technical Problem

The existing thermoplastic resin films for metal tanks have shortcomings in corrosion resistance and heat resistance, especially when treating acidic contents under high temperature and high pressure, and are more costly.

Method used

The extremely thin polyethylene terephthalate (PET) film is used to replace it with the polyethylene naphthalate (PEN) film. By controlling its thickness and heat shrinkage, combined with appropriate heat setting treatment, it ensures high corrosion resistance and good adhesion.

Benefits of technology

Good corrosion resistance and adhesion to acidic contents under high temperature and high pressure is achieved, while reducing the cost per unit area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627997000001
    Figure 0007627997000001
  • Figure 0007627997000002
    Figure 0007627997000002
Patent Text Reader

Abstract

To provide a film for pasting to metal which is excellent in adhesion with a steel plate when having used a polyethylene naphthalate film as an extremely thin film, and comprises high corrosion resistance when having given retort processing to acid contents.SOLUTION: A polyethylene film for pasting to metal in which resin is mainly composed of polyethylene-2,6-naphthalate, and a heat shrinkage rate under 5-14 μm of thickness, and 150°C for 30 minutes is 2.7% or less in the longitudinal direction and the direction perpendicular thereto (the width direction).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film for metal lamination processing. More specifically, the present invention relates to a polyethylene-2,6-naphthalene dicarboxylate film, which is a biaxially oriented thin film that has excellent retort brushing resistance, lid-tightening processability, and corrosion resistance after processing, particularly in severe advanced processing such as drawing and ironing, and is suitable for producing metal cans such as beverage cans and food cans. [Background technology]

[0002] Metal cans are generally painted to prevent corrosion on the inside and outside, but in recent years, with the aim of simplifying the process, improving hygiene, and preventing pollution, efforts have been made to develop methods for obtaining rust prevention without using organic solvents, and one such attempt is to cover metal cans with thermoplastic resin films. That is, studies are being made on a method in which a thermoplastic resin film is laminated onto a metal plate such as tinplate, tin-free steel, or aluminum, and then the can is made by drawing or other processing.

[0003] In particular, polyethylene terephthalate film has attracted attention as a film with well-balanced properties, and several proposals based on this film have been made (Patent Documents 1 to 6). However, these proposals do not satisfy all of the requirements for moldability, heat resistance, aroma retention, impact resistance, and corrosion resistance.

[0004] In this situation, Patent Document 7 proposes the use of a polyethylene-2,6-naphthalate film instead of a polyethylene terephthalate film as a film having excellent taste retention and retort resistance, and specifically discloses a polyethylene naphthalate film having a thickness of 25 μm that is stretched 3 times by 3 times in the longitudinal and transverse directions and heat-set at 180°C.

[0005] However, polyethylene naphthalate films are much more expensive than polyethylene terephthalate films, and have not been put to practical use. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2003-238780 A [Patent Document 2] JP 2002-88233 A [Patent Document 3] JP 2001-335682 A [Patent Document 4] JP 2007-203569 A [Patent Document 5] JP 2002-178471 A [Patent Document 6] JP 2003-231231 A [Patent Document 7] Japanese Patent Application Publication No. 10-130403 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a film for metal lamination processing which has excellent adhesion to steel sheets and a high degree of corrosion resistance when subjected to retort treatment with acidic contents. [Means for solving the problem]

[0008] It was generally expected that the corrosion resistance would deteriorate as the film was made thinner, but in the case of polyethylene naphthalate film, contrary to expectations, it was found that by combining extremely thinning the film with controlling the heat shrinkage rate, the corrosion resistance was maintained while the adhesion was also improved. Moreover, by being able to make the film thinner, the cost per unit area can be reduced.

[0009] That is, the present invention is achieved by the following configuration requirements. 1. A polyester film for metal lamination processing, whose main component is polyethylene-2,6-naphthalate, whose thickness is 5 to 14 μm and whose thermal shrinkage rate at 150°C for 30 minutes is 2.7% or less in both the longitudinal direction and the direction perpendicular to that (width direction). 2. The polyester film for metal lamination processing according to 1 above, which has a glass transition point of 100° C. or higher. 3. The polyester film for metal-laminated molding processing according to 1 or 2 above, wherein the metal-laminated container is a container used for retort treatment of acidic contents. Effect of the Invention

[0010] The metal lamination molding film of the present invention uses a very thin polyethylene naphthalate film of 14 μm or less and has a specific range of heat shrinkage under specific conditions, which gives it excellent adhesion to steel plates and a high level of corrosion resistance when subjected to retort treatment with acidic contents. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The components constituting the film for metal lamination forming of the present invention, the preparation method, etc. will be specifically described below in order.

[0012] <Film for metal lamination molding> The film for metal lamination molding of the present invention is a polyester film for metal lamination molding that is mainly composed of polyethylene-2,6-naphthalate, has a thickness of 5 to 14 μm, and has a heat shrinkage rate of 2.7% or less in both the longitudinal direction and the direction perpendicular thereto (width direction) at 150°C for 30 minutes.

[0013] Here, "mainly" indicates that the polyester derived from the polyethylene-2,6-naphthalate component is, for example, 50% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more, based on the weight of the total resin composition.

[0014] In the resin of the polyester film for metal lamination processing of the present invention, the polyethylene-2,6-naphthalate component is the main component, so that the film has a high level of corrosion resistance when acidic contents are retorted. If the ratio of the polyester derived from the polyethylene-2,6-naphthalate component is lower than the lower limit, a high level of corrosion resistance cannot be obtained when the film for metal lamination processing is made.

[0015] The polyester film for metal lamination processing of the present invention is preferably a single-layer film, but may be a film having two or more layers.

[0016] The polyester film for metal lamination processing of the present invention is not particularly limited as long as it satisfies the above-mentioned composition ratio requirements, and may be a homopolyester or a copolymer polyester. A preferred example of the homopolyester is homopolyethylene-2,6-naphthalate, and a preferred example of the copolymer polyester is a polyethylene-2,6-naphthalate copolymer.

[0017] The copolymerization component of the copolymerized polyester can be preferably an acid component or a diol component. As the acid component, aromatic dicarboxylic acids such as isophthalic acid, phthalic acid, terephthalic acid, diphenyl ether dicarboxylic acid, etc. other than the main acid component such as 2,6-naphthalenedicarboxylic acid, aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, oxalic acid, succinic acid, etc., and oxycarboxylic acids such as p-oxybenzoic acid, p-oxyethoxybenzoic acid, etc. are preferred, and as the diol component, aliphatic diols such as propylene glycol, trimethylene glycol, 1,6-hexanediol, and alicyclic diols such as 1,4-hexamethylene dimethylethanol are preferably used. These can be used alone or in combination. Among these, terephthalic acid is more preferred as the acid component.

[0018] The polyester film for metal lamination processing in the present invention is mainly composed of polyethylene naphthalate, and the lower limit of the glass transition temperature (abbreviated as Tg) when the film is melted and held at 300°C for 3 minutes, then quenched, and then heated at 20°C / min is preferably 100°C or more, more preferably 110°C or more, and even more preferably 115°C or more. On the other hand, the upper limit of Tg is preferably 125°C or less, more preferably 123°C or less, and even more preferably 121°C or less. When Tg is lower than the lower limit, when the metal to which the film is laminated is processed into a container, and highly acidic contents such as pickles are filled in the container and retorted at high temperature, the molecules in the film become more mobile at high temperature, so that the content liquid penetrates the film and rusts the metal part, which is not preferable. On the other hand, when Tg exceeds the upper limit, the amount of heat required for the film to thermally adhere during lamination is not sufficiently given, resulting in poor adhesion, which is not preferable.

[0019] (Method of producing polyethylene-2,6-naphthalate resin) Next, a method for producing the polyester resin in the polyester film for metal lamination processing of the present invention will be described.

[0020] First, the method for producing the polyester resin in the polyester film for metal lamination processing of the present invention comprises, for example, a first reaction in which an aromatic dicarboxylic acid or its ester-forming derivative is subjected to an esterification reaction or an ester exchange reaction with an alkylene glycol to synthesize a polyester precursor, and a second reaction in which the precursor is subjected to a polycondensation reaction, and a method known per se can be adopted.

[0021] The polyethylene-2,6-naphthalate used as a specific raw material of the polyester resin in the polyester film for metal lamination processing of the present invention is a compound having a repeating unit composed of ethylene-2,6-naphthalate, and can be produced by esterifying and polymerizing naphthalene-2,6-dicarboxylic acid or a derivative thereof with ethylene glycol in the presence of a catalyst under appropriate reaction conditions.

[0022] As for the preferred conditions for the first reaction, the reaction may be carried out under normal pressure, but it is preferred to carry out the reaction under a pressure of 0.05 MPa to 0.5 MPa, since this makes it easier to increase the reaction rate. The temperature of the first reaction is preferably in the range of 210°C to 270°C. By keeping the reaction pressure within the above range, the reaction can be easily promoted while suppressing the generation of by-products, such as dialkylene glycol. In this case, it is preferred to use 1.1 to 6 molar times of the alkylene glycol component relative to the acid component present in the reaction system in which the first reaction is carried out, from the viewpoints of reaction rate and maintaining the physical properties of the resin. More preferably, it is 2 to 5 molar times, and even more preferably, it is 3 to 5 molar times.

[0023] In order to increase the reaction rate of the first reaction, it is preferable to use a catalyst known per se, such as a metal compound having a metal component such as Li, Na, K, Mg, Ca, Mn, Co, or Ti. Among these, when the reaction is carried out under pressure, Mn or Ti compounds are preferable from the viewpoint of the ease of reaction. In particular, Ti compounds are preferable because they can also be used as polycondensation reaction catalysts and cause little precipitation of catalyst residues. As the titanium compound used in the present invention, an organic titanium compound soluble in polyester is preferable from the viewpoint of suppressing the generation of insoluble coarse foreign matter due to precipitation of catalyst residues. Particularly preferable titanium compounds include titanium tetraisopropoxide, titanium tetrapropoxide, titanium tetrabutoxide, titanium tetraethoxide, titanium tetraphenoxide, and titanium trimellitate.

[0024] The amount of catalyst to be added is preferably 10 to 150 millimol% in terms of metal element based on the mole number of all acid components present in the first reaction, more preferably 20 to 100 millimol%, and particularly preferably 30 to 70 millimol%, because it can promote the reaction rate while suppressing the generation of coarse insoluble foreign matter caused by the catalyst, and furthermore, can maintain the heat resistance of the copolymerized aromatic polyester obtained to a high degree. When adding a titanium compound, it is preferable to add it so that it is present from the start of the esterification reaction of the first reaction, and as described above, it is used as a polycondensation reaction catalyst continuously. Of course, it may be added in two or more portions in order to control the polycondensation reaction rate.

[0025] Next, the second reaction in which the precursor obtained in the first reaction is subjected to a polycondensation reaction will be described.

[0026] In order to impart high thermal stability to the resin in the polyester film for metal lamination processing in the present invention, it is preferable to add a thermal stabilizer consisting of a phosphorus compound to the reaction system before the start of the polycondensation reaction in the second reaction. Specific phosphorus compounds are not particularly limited as long as they have phosphorus elements in the compound, and examples thereof include phosphoric acid, phosphorous acid, trimethyl phosphate, tributyl phosphate, triphenyl phosphate, monomethyl phosphate, dimethyl phosphate, phenylphosphonic acid, dimethyl phenylphosphonic acid, diethyl phenylphosphonic acid, ammonium phosphate, triethyl phosphonoacetate, and methyl diethyl phosphonoacetate, and these phosphorus compounds may be used in combination of two or more. The timing of adding the phosphorus compound is preferably between the substantial end of the first reaction and the beginning of the polycondensation reaction, which is the second reaction, and the addition may be performed at once or in two or more divided portions.

[0027] When producing the polyester resin in the polyester film for metal lamination processing of the present invention, the temperature of the polycondensation reaction is preferably in the range of 270°C to 300°C, and the pressure during the polycondensation reaction is preferably under reduced pressure of 50 Pa or less. If the pressure during the polycondensation reaction is higher than the upper limit, the time required for the polycondensation reaction will be long and it will be difficult to obtain a copolymerized aromatic polyester with a high degree of polymerization. As the polycondensation catalyst, known metal compounds such as Ti, Al, Sb, and Ge can be suitably used, and among them, it is preferable to continue using the titanium compound added during the esterification reaction or the ester exchange reaction, since this can suppress the generation of insoluble coarse foreign matter due to catalyst residue.

[0028] If necessary, these may contain other additives such as a fluorescent whitening agent, an antioxidant, a heat stabilizer, and an antistatic agent.

[0029] (wax) The polyester composition constituting the metal laminated molding film of the present invention may contain wax. Preferred examples of wax include vegetable waxes such as carnauba wax, candelilla wax, rice wax, wood wax, jojoba oil, palm wax, rosin modified wax, ouricury wax, sugarcane wax, esparto wax, and bark wax; animal waxes such as beeswax, lanolin, whale wax, ivoro wax, and shellac wax; mineral waxes such as montan wax, ozokerite, and ceresin wax; petroleum waxes such as paraffin wax, microcrystalline wax, and petroleum waxes such as petroleum wax; and synthetic hydrocarbon waxes such as Fischer-Tropsch wax, polyethylene wax, oxidized polyethylene wax, polypropylene wax, and oxidized polypropylene wax. Among these, it is more preferable to use a wax having a softening point of 120° C. or more, since the wax component is less likely to be dissolved in food even during high-temperature retort treatment.

[0030] In addition, the polyester composition constituting the metal lamination forming film of the present invention preferably contains an incompatible wax, which can roughen the surface of the film, improving the slipperiness during can processing and making the film less likely to be scraped. In particular, polyethylene wax is most preferred because it can provide good hygiene in packaging food applications.

[0031] In the metal laminated forming film of the present invention, the wax content is preferably 0.01 to 1.0% by weight, more preferably 0.05 to 0.3% by weight, based on 100% by weight of the polyester composition. If the wax content is less than the lower limit, the abrasion resistance during can forming becomes insufficient, which is not preferred. On the other hand, if the wax content is more than the upper limit, not only will the quality be excessive, but the wax will bleed out during the film forming, laminating, and can forming processes, which is not preferred, and therefore the processes will be contaminated.

[0032] (particle) The polyester film for metal lamination processing of the present invention is preferably blended with fine particles in order to improve the handling property, particularly the winding property, in the film production process. The amount of the fine particles is preferably 0.01 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, based on 100 parts by weight of the polyester resin.

[0033] The fine particles may be either inorganic or organic fine particles, and more preferably inorganic fine particles. Preferred examples of inorganic fine particles include silica, alumina, titanium dioxide, calcium carbonate, and barium sulfate. Preferred examples of organic fine particles include crosslinked polystyrene particles and crosslinked silicone resin particles. Among them, non-spherical porous silica is more preferred because it is less likely to generate voids around the particles when the film is stretched, and therefore has the characteristic of improving the transparency and glossiness of the film.

[0034] The average particle size of the fine particles is preferably 0.1 to 3.0 μm, more preferably 0.3 to 2.0 μm. If the average particle size is less than the lower limit, the amount of addition must be increased to obtain the transportability of the film, i.e., the slipperiness, and transparency is undesirably impaired. On the other hand, if the average particle size exceeds the upper limit, coarse particles in the portion deformed by molding may become the starting point for pinholes or, in some cases, cause breakage, which is undesirable.

[0035] (Other additives) In the metal lamination molding film of the present invention, other additives such as colorants, antioxidants, heat stabilizers, ultraviolet absorbers, antistatic agents, etc. can be blended into the polyethylene-2,6-naphthalate as necessary within the scope of the present invention. In particular, for the purpose of obtaining a white appearance, it is preferable to use a known technique such as incorporating titanium oxide. However, a transparent film is more preferable because it provides a superior glossy feel after laminating the film and metal plate.

[0036] In particular, in order to give a high-end appearance, a gold color may be applied, and for this purpose, a colorant, particularly a yellow colorant, may be added to the film. The yellow colorant is preferably an anthraquinone type, an isoindolinone type, a benzimidazolone type, a quinophthalone type, or a condensed azo type, and more preferably an isoindolinone type.

[0037] The content of the color pigment is preferably more than 10% by weight and not more than 50% by weight, more preferably 15 to 40% by weight, and particularly preferably 15 to 30% by weight. If the content of the color pigment is less than the lower limit, the hiding power is poor, and if it exceeds the upper limit, not only the hiding power improvement effect is saturated, but also the film becomes brittle and easily breaks during film stretching, and cracks and breaks easily occur when the obtained film is laminated to a metal plate and then molded into a can, which is not preferable. As the colorant, other components may be used in combination to adjust the color tone, but it is preferable to use a colorant having good heat resistance and having been recognized as safe from the standpoint of food hygiene for its intended use.

[0038] The wax component and other additives may be added during the polymerization process of the raw resin, or a resin composition containing additives at a desired concentration may be obtained by producing high-concentration master chips using, for example, a twin-screw extruder and diluting them with additive-free chips. The additives may also be added directly in powder form to the extruder in the film-forming process using, for example, a screw feeder.

[0039] (Layer composition) The film for metal lamination processing of the present invention is preferably a biaxially oriented monolayer film mainly made of polyethylene-2,6-naphthalenedicarboxylate, but is preferably a laminated film in order to impart design and slip properties. To impart design properties, for example, a polyester layer A mainly made of polyethylene-2,6-naphthalenedicarboxylate and a polyester layer B in contact with this layer A are added with a pigment, and a two-layer film is formed by a co-extruder. Similarly, particles can be added to the polyester layer B to impart slip properties. The surface to be laminated to the metal may be the polyester layer A or the polyester layer B, but it is preferably the polyester layer A with a low amount of additives added.

[0040] (laminate) The film for metal lamination processing of the present invention is laminated to a metal plate. The metal plate to which the laminated film for metal lamination processing of the present invention is to be laminated is, for example, a metal plate for can manufacturing, and specifically, for example, tinplate, tin-free steel, tin-nickel steel, and aluminum plates are preferable. The polyester film is laminated to the metal plate by a method in which the metal plate is heated to a temperature equal to or higher than the melting point of the film, the film is laminated, and then cooled to make the surface layer (thin layer) of the film in contact with the metal plate amorphous and adhered to the metal plate, and also by a method in which the film is primer-coated with an adhesive in advance and this surface is laminated to the metal plate. It is preferable to use a known resin adhesive as the adhesive, for example, an epoxy adhesive, an epoxy-ester adhesive, or an alkyd adhesive. In addition, a white pigment or a yellow pigment may be dispersed in the adhesive to make the film have a colored appearance.

[0041] (Thickness) The metal laminated forming film of the present invention must have a thickness of 5 to 14 μm. If the thickness is less than the lower limit, the adhesion to the steel plate decreases, and the film is easily torn during forming, resulting in poor rust prevention for the steel plate. If the thickness exceeds the upper limit, the thermal shrinkage rate when heat-treated at 150°C for 30 minutes exceeds the upper limit in the longitudinal direction and in the direction perpendicular thereto (width direction), resulting in increased residual stress, causing poor adhesion to the metal and reduced corrosion resistance. If the thickness exceeds the upper limit, unmelted material remains when the film is melt-bonded during lamination, and the film is prone to cracking during forming. The thickness of the film was measured using a dot thickness gauge.

[0042] (Film manufacturing method) The manufacturing method of the film for metal lamination processing of the present invention described above is not particularly limited, and an unstretched film may be first prepared by a conventionally known film-forming method, and then stretched in two directions. For example, the film can be produced by a process of co-extruding the polymer in a molten state from a die into a sheet, a process of cooling and solidifying the obtained sheet-like material to form an unstretched polyester film, and a process of stretching the obtained unstretched polyester film in the film-forming direction and the width direction. The temperature in the molten extrusion process is not particularly limited as long as there is no unmelted material and the heat deterioration of the polyester does not progress excessively, and it is preferable to perform the process in a temperature range of, for example, the melting point of the polyester (Tm: ° C.) to (Tm + 70) ° C. Next, in order to maintain the flatness of the obtained unstretched polyester film while reducing thickness unevenness, it is preferable to use a rotating cooling drum installed below the die along the film-forming direction and cool the sheet-like material by adhering it to it. Next, for the stretching, the unstretched polyester film is stretched in one axial direction (longitudinal or transverse direction) at a temperature of (glass transition temperature (Tg) of polyester -10)°C to (Tg+60)°C at a ratio of preferably 2.5 times or more, more preferably 2.8 times or more, and then stretched in a direction perpendicular to the stretching direction at a temperature of Tg to (Tg+60)°C at a ratio of preferably 2.5 times or more, more preferably 3 times or more. The transverse stretching temperature is preferably in the range of (Tg+25) to (Tg+60°C), more preferably (Tg+30) to (Tg+60°C), further preferably (Tg+30) to (Tg+55°C), and most preferably (Tg+35) to (Tg+55°C). In this case, the transverse stretching temperature is preferably increased stepwise, and it is preferable that each temperature is within the above range. If the transverse stretching temperature is too low relative to Tg, excessive stress during stretching is concentrated on the particles, and as a result, the voids around the particles become larger, making the protrusions taller and larger, and more likely to break. If necessary, the film may be stretched again in the longitudinal and / or transverse directions. The total stretch ratio when stretched in this manner is preferably 7 times or more, more preferably 8 to 15 times, and even more preferably 8 to 12 times, in terms of area stretch ratio (longitudinal stretch ratio x transverse stretch ratio).If the temperature is less than the lower limit, molecular orientation does not proceed, resulting in a film with poor thickness unevenness, which is not preferred. If the temperature is greater than the upper limit, orientation proceeds too much, resulting in poor adhesion to the steel sheet, which is also not preferred. The biaxially oriented film is preferably heat-set at a temperature of (Tm-80) to (Tm-60)°C. Specifically, heat-setting at 185 to 210°C is preferred. The heat-setting time is preferably 0.1 to 60 seconds. Although the above-mentioned stretching has been explained as sequential biaxial stretching, simultaneous biaxial stretching in which the film is stretched simultaneously in the longitudinal and transverse directions may also be used.

[0043] Furthermore, the heat treatment is preferably performed at a temperature (Tg-20) to (Tm-80)°C lower than the heat setting temperature, specifically, at a temperature in the range of preferably 100 to 180°C, more preferably 110 to 160°C, and preferably under relaxation of 5% or less, whereby a biaxially stretched laminate film for metal lamination molding of the present invention can be obtained.

[0044] (Physical properties) [Heat shrinkage rate] The heat shrinkage of the polyester film for metal lamination processing of the present invention must be 2.7% or less in both the longitudinal direction and the direction perpendicular thereto (width direction) under conditions of 150° C. and 30 minutes. If the heat shrinkage when the film is held in an atmosphere of 150° C. for 30 minutes exceeds the upper limit, residual stress is generated in the film due to the heat during lamination when the film is laminated to the metal, reducing the adhesion to the metal and causing the film to peel off from the metal, which is undesirable.

[0045] When the heat shrinkage rate is equal to or lower than the upper limit, the adhesion between the metal and the film is good, and high-order processability can be maintained. The thermal shrinkage rate was measured by preparing a 30 cm square film, holding it at a predetermined temperature for a predetermined time and allowing it to freely shrink, and measuring the shrinkage rate.

[0046] [Glass transition temperature] The glass transition temperature (Tg) of the polyester film for metal lamination processing of the present invention is preferably 100°C or higher. If the temperature is lower than this temperature, when highly acidic contents such as pickles are retorted at high temperatures, the molecules in the film become more mobile at high temperatures, so the liquid in the contents penetrates the film and rusts the metal parts, which is not preferable. A higher glass transition temperature is preferable, but a higher glass transition temperature often results in a higher melting point. If the melting point exceeds 275°C, the heat required for the film to thermally adhere during lamination is not sufficiently provided, resulting in poor adhesion, which is not preferable. A preferred glass transition temperature is 125°C or lower. The glass transition temperature was measured using a differential scanning calorimeter DSC Q100 manufactured by TA Instruments. The glass transition temperature was determined by a method in which the film was kept molten at 290°C for 3 minutes, then rapidly cooled and then reheated. The measurement sample was 20 mg weighed out from the film.

[0047] [Face orientation coefficient] The plane orientation coefficient of the polyester film for metal lamination processing of the present invention is preferably 0.230 to 0.251. If the plane orientation coefficient is less than the lower limit, the thickness unevenness of the film will be worse and the heat shrinkage will exceed 3%, which is not preferable because it will reduce the adhesion to the steel plate. If the plane orientation coefficient exceeds the upper limit, it is not preferable because it may cause unmelted residue after lamination to the metal and reduce the corrosion resistance. The plane orientation coefficient is given by the following formula. ns = (nTD + nMD) / 2 - (nz) Here, ns is the plane orientation coefficient, nTD is the refractive index in the horizontal direction of the film, nMD is the refractive index in the vertical direction, and nz is the refractive index in the thickness direction of the film. These refractive indices were obtained by measuring the refractive index at a wavelength of 633 nm using a prism coupler manufactured by Metricon, and were used as the refractive index in each direction.

[0048] [density] The density of the polyester film for metal lamination processing of the present invention is preferably 1.350 to 1.356 g / cm 3Within this range, the film thickness unevenness can be suppressed, and the film is suitable for lamination, which is preferable. If the density is below the lower limit, it is difficult to adjust the film thickness unevenness when the film is formed, and air bubbles are trapped during lamination, which is undesirable. If the lamination transport time is slowed down to compensate for the poor thickness unevenness, crystallization will progress, and the adhesion will decrease, which is undesirable. If the density exceeds the upper limit, some of the film may remain undissolved after being laminated to metal, which is undesirable because the corrosion resistance will decrease. The film density referred to here means a value measured at 30°C by a density gradient tube method using a calcium nitrate solution.

[0049] [Intrinsic viscosity] Next, the intrinsic viscosity of the polyester film for metal lamination processing of the present invention is preferably 0.53 to 0.65, more preferably 0.56 to 0.62. If the intrinsic viscosity is less than the lower limit, the film formability decreases, and a film having mechanical strength sufficient for practical use cannot be obtained, which is undesirable. On the other hand, if the intrinsic viscosity is more than the upper limit, the molding processability is impaired, which is undesirable.

[0050] Here, the intrinsic viscosity (IV) of the polyester film for metal lamination processing of the present invention was determined by dissolving the raw material polyester composition used for film formation in o-chlorophenol, removing color pigments and the like using a centrifuge, measuring the solution at 35°C, and substituting the value (IVa) obtained into the following formula (2) as a value converted into the weight of the resin content. IV=IVa / (1-C) ---(2) Here, C refers to the color pigment concentration of each layer.

[0051] [Peak melting temperature] Next, the melting peak temperature of the polyester film for metal lamination processing of the present invention is preferably 240 to 275° C., more preferably 265 to 270° C. If the melting peak temperature is below the lower limit, the corrosion resistance decreases, while if it exceeds the upper limit, the amount of heat required for the film to thermally adhere during lamination is not sufficiently imparted, resulting in poor adhesion, which is undesirable.

[0052] The melting points of the polyester film for metal lamination molding of the present invention and the polyester film after melting are melting points obtained by a differential scanning calorimeter DSC Q100 manufactured by TA Instruments Co., Ltd. A 20 mg sample was heated to 300°C at a heating rate of 20°C / min, kept molten at 300°C for 3 minutes, then quenched, and heated again at 20°C / min to measure the melting peak temperature.

[0053] [Adhesion to metal] Next, the adhesion of the polyester film for metal lamination processing of the present invention to metal was measured by laminating the film of the present invention to the outer surface of a tin-free steel plate having a thickness of 0.25 mm preheated to 230° C. by pressing with a nip roll, and immediately quenching in a water tank to obtain a laminated steel plate. A rectangular test piece having a width of 15 mm was cut out from this laminated metal plate, and a 180° peel test was performed at a speed of 10 mm / min. The adhesion was evaluated according to the following criteria, preferably 10 N / 15 mm or more and less than 14 / N15 mm, and more preferably 14 N / 15 mm or more. If the adhesion index is less than 10 N / 15 mm, it is not preferable because it is prone to cohesive failure.

[0054] [Retort resistance] Next, the retort resistance of the polyester film for metal lamination molding of the present invention was evaluated by placing the can obtained by the seaming process in a retort oven, retorting the sample for 30 minutes with pressurized steam at 125°C while preventing the steam from directly hitting the sample, and visually evaluating the appearance of the film according to the following criteria: A slight cloudiness is preferable, no change is more preferable, and a significant spotted milky white change in the retort resistance index is considered unfavorable.

[0055] [Corrosion resistance (soundness after retort)] Next, the corrosion resistance of the polyester film for metal lamination processing of the present invention was evaluated by punching a film-laminated metal plate into a disk shape by a known press molding process and forming it into a desired lid shape to obtain a can, which was then filled with 3% acetic acid + 2% saline and retorted for 90 minutes in the above sterilizer with pressurized steam at 125°C. The can was then removed and the condition inside the can was visually confirmed.

[0056] Preferably, partial corrosion of the steel plate or peeling of the film occurs in any of the 10 cans, more preferably, no corrosion of the steel plate occurs in any of the 10 cans but minor film blistering occurs in any of the 10 cans, and even more preferably, no corrosion of the steel plate or peeling of the film occurs in any of the 10 cans. If the corrosion resistance index is such that full corrosion of the steel plate and peeling of the film occurs in any of the 10 cans, this is not preferable because it will cause the can wall to rust when highly acidic food is filled in the can.

[0057] [Deep drawing processability] Next, the deep drawing processability of the polyester film for metal lamination processing of the present invention was evaluated by laminating the obtained film by pressing with a nip roll to the outer surface of a tin-free steel plate having a thickness of 0.25 mm preheated to 230°C, cutting the obtained laminated metal plate into a disk shape having a diameter of 150 mm, and deep drawing the laminated side to the inner surface using a drawing die and a punch in four stages to produce a seamless container having a diameter of 55 mm (hereinafter referred to as a can). The processing state of this can was observed and visually evaluated according to the following criteria.

[0058] Preferably, whitening or peeling is observed on the upper part of the film can, and more preferably, the film is processed without any abnormality and whitening or breakage is not observed in the film. If breakage is observed in a part of the film, it is not preferable because the corrosion resistance is significantly reduced.

[0059] [Tightening processability] Next, the fastening processability of the polyester film for metal lamination processing of the present invention was evaluated by punching out the film-laminated metal plate into a disk shape by a known press molding process and forming it into a desired lid shape, and then fastening it to the top of the can produced in the deep drawing processability evaluation using a fastening machine. The processing state of this lid material was observed at the fastening part and visually evaluated according to the following criteria. Preferably, no abnormality (cracks, tears, peeling from the plate) was observed in the film. If an abnormality (cracks, tears, peeling from the metal plate) occurs in a part of the film, the corrosion resistance is significantly reduced, which is not preferable. EXAMPLES

[0060] The present invention will be further described below with reference to examples. The film properties were measured and evaluated by the following methods. (1) Peak melting temperature of the resin composition Measurement was performed using a 20 mg sample using a differential scanning calorimeter DSC Q100 manufactured by TA Instruments. The sample was heated to 300°C at a heating rate of 20°C / min, held in the melt at 300°C for 3 minutes, then rapidly cooled, and heated again at 20°C / min to determine the melting peak temperature. (2) Glass transition temperature (Tg) of the resin composition The glass transition temperature and the crystallization peak temperature were determined in the same manner as in (1) above (note that the sample amount was 20 mg). (3) Intrinsic viscosity 0.3 g of the film was dissolved in 25 ml of o-chlorophenol, cooled, and the solution was measured at 35° C. using an Ostwald viscosity tube, from which the viscosity was calculated. (4) Adhesion to metals The film of the present invention was laminated by pressing with a nip roll onto the outer surface of a 0.25 mm thick tin-free steel sheet preheated to 230°C, and immediately quenched in a water tank to obtain a laminated steel sheet. A rectangular test piece 15 mm wide was cut out from this laminated metal sheet, and a 180° peel test was performed at a speed of 10 mm / min, and the results were evaluated according to the following criteria. 〇: 14N / 15mm or more △: 10N / 15mm or more, 14 / N less than 15mm ×: Less than 10N / 15mm (5) Deep drawing processability The laminated metal sheet obtained in (4) was cut into a disk shape with a diameter of 150 mm, and deep-drawn in four stages using a drawing die and a punch with the laminate side facing inside to produce a 55 mm diameter seamless container (hereinafter referred to as a can). The results of observing the processing state of this can were visually evaluated according to the following criteria. ◯: The film was processed without any abnormality, and no whitening or breakage was observed in the film. △: Whitening or peeling was observed on the upper part of the film can. ×: Part of the film was broken. (6) Seaming processability The film-laminated metal plate was punched into a disk shape by a known press molding process and formed into the desired lid shape, and then it was wrapped around the top of the can produced in (5) using a seaming machine. The processing state of this lid material was observed at the seamed part and visually evaluated according to the following criteria. ○: No abnormality (cracks, tears, peeling from the plate) was observed in the film. ×: Abnormalities occurred in part of the film (cracks, tears, peeling from the metal plate). (7) Retort resistance The can obtained in (6) above was placed in a retort oven and retorted for 30 minutes with pressurized steam at 125° C. while preventing the steam from directly hitting the sample, and the appearance of the film was visually evaluated. ○: No change. △: Slightly cloudy. ×: Significant spots were changed to milky white. (8) Corrosion resistance (post-retort integrity) evaluation The cans obtained in (6) above were filled with 3% acetic acid + 2% saline solution and retorted in the above sterilizer with pressurized steam at 125°C for 90 minutes. The cans were taken out and the condition inside the cans was visually confirmed. ◎: No corrosion of the steel plate or peeling of the film for all 10 pieces ○: Of the 10 samples, there was no corrosion of the steel plate, but a small film blister occurred. △: Partial corrosion of the steel plate or peeling of the film occurred in any of the 10 cases. ×: Of the 10 samples, corrosion occurred on the entire surface of the steel plate and the film peeled off.

[0061] [Example 1] A mixture of 100 parts of 2,6-dimethylnaphthalate and 56 parts of ethylene glycol was charged with 0.0313 parts of manganese acetate tetrahydrate in a SUS (stainless steel) vessel capable of pressure reactions. The mixture was pressurized to 0.07 MPa and heated from 140°C to 240°C to carry out an ester exchange reaction. After that, 0.042 parts of triethylphosphonoacetate was added to terminate the ester exchange reaction.

[0062] The reaction product was then transferred to a polymerization vessel, and 0.15% by weight of spherical silica particles having an average particle size of 0.3 μm was added as a lubricant. The temperature was raised to 290° C., and 0.0239 parts of antimony trioxide was added, followed by polycondensation reaction at a high vacuum of 100 Pa to obtain a polyethylene-2,6-naphthalate resin composition having an intrinsic viscosity of 0.62 and a diethylene glycol content of 1.5 mol % (relative to the 2,6-ethylene naphthalate component).

[0063] The resin composition was pelletized, and the pellets were dried at 170°C for 6 hours. The pellets were then fed into an extruder hopper, where they were heat-melted in the extruder and co-extruded into a sheet from a die onto a cooling drum at a melt temperature of 310°C to obtain an unstretched polyester film.

[0064] The unstretched polyester film thus obtained was preheated to 120°C, heated from above with an IR heater so that the film surface temperature became 140°C, and stretched in the machine direction (film-forming direction) at a stretch ratio of 3.1 times. Next, it was fed into a stenter heated to 155°C, and stretched 3.0 times in the transverse direction (first stage) while increasing the temperature stepwise to 165°C and 170°C, and then fed into a stenter heated to 180°C and stretched again 1.1 times in the transverse direction, and then heat-set with hot air at 195°C for 4 seconds to obtain a biaxially oriented polyester film with a thickness of 9 μm. The obtained biaxially oriented polyester film had an intrinsic viscosity of 0.59 dl / g, a Tg of 120.5°C, no subpeak due to thermal fixation, a melting point of 269.6°C, a planar orientation coefficient of 0.240, and a 30-minute heat shrinkage rate of 2.1% in the longitudinal direction and 1.8% in the direction perpendicular to the longitudinal direction. The properties of the resulting biaxially oriented polyester film are shown in Table 1.

[0065] [Example 2, Comparative Examples 1, 2, 3] Biaxially oriented polyester films were obtained in the same manner as in Example 1, except that the stretching ratio and heat setting temperature were changed. The properties of the obtained biaxially oriented polyester films are shown in Table 1. The evaluation results of these films are shown in Table 2. It was found that the cans using the polyester film of the present invention had excellent adhesion to metal plates and corrosion resistance.

[0066] [Table 1]

[0067] [Table 2]

[0068] PEN: Polyethylene-2,6-naphthalate PET; Polyethylene terephthalate

[0069] [Comparative Example 4] After drying the polyethylene terephthalate pellets at 170°C for 6 hours, they were fed into an extruder hopper, and the pellets were heat-melted in the extruder, and co-extruded from a die onto a cooling drum at a melting temperature of 310°C into a sheet-like shape to obtain an unstretched polyester film. The unstretched polyester film thus obtained was preheated to 120°C, heated from above with an IR heater so that the film surface temperature became 140°C, and stretched in the longitudinal direction (film-forming direction) at a stretching ratio of 3.6 times. Then, it was fed into a stenter heated to 155°C, and while increasing the temperature stepwise to 165°C and 170°C, it was stretched 4.1 times in the transverse direction (first stage), and then further fed into a stenter heated to 180°C and stretched again 1.1 times in the transverse direction, and then heat-set with hot air at 200°C for 4 seconds to obtain a biaxially oriented polyester film having a thickness of 9 μm.

[0070] The properties of this polyethylene terephthalate are shown in Table 1. The corresponding polyethylene terephthalate film was formed and laminated to a metal in the same manner to evaluate the corrosion resistance, but rust was generated on the metal after retort treatment, so it is not suitable for the application area of ​​the present invention. [Industrial Applicability]

[0071] The polyester film for metal lamination processing of the present invention is excellent in corrosion resistance after processing when a thin film is used, and therefore can be suitably used for applications such as beverage cans and food cans.

Claims

1. A polyester film for metal lamination molding processing, which contains 90% by weight or more of polyethylene 2,6-naphthalate based on the weight of the total resin composition, has a thickness of 5 to 14 μm, has a thermal shrinkage rate at 150°C for 30 minutes of 2.7% or less in both the longitudinal direction and the direction perpendicular thereto (width direction), and has a glass transition point of 100°C or higher.

2. 2. The polyester film for metal-laminated molding according to claim 1, wherein the metal-laminated container is a container used for retort treatment of acidic contents.

Citation Information

Patent Citations

  • Polyester film for covering metal

    JP1997052337A

  • Polyester film for lamination with metallic sheet or plate

    JP1998130403A

  • Substrate film for lamination to metal sheet

    JP2000103881A

  • Polyester film for laminating metal plate

    JP2001335682A

  • Polyester film for metal sheet lamination, laminated metal sheet, and metal container using the same

    JP2002088233A